2020
DOI: 10.1126/science.aaz5192
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing rhizosphere microbiomes for drought-resilient crop production

Abstract: Root-associated microbes can improve plant growth, and they offer the potential to increase crop resilience to future drought. Although our understanding of the complex feedbacks between plant and microbial responses to drought is advancing, most of our knowledge comes from non-crop plants in controlled experiments. We propose that future research efforts should attempt to quantify relationships between plant and microbial traits, explicitly focus on food crops, and include longer-term experiments under field … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
419
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 591 publications
(430 citation statements)
references
References 66 publications
8
419
3
Order By: Relevance
“…Scientists have isolated rhizospheric and endophytic bacteria and fungi from arid regions or from xerophytes, and these microbes have been shown to improve the growth of rice, sorghum, corn, cabbage, millet, and wheat under drought-stress conditions [ 14 , 80 , 81 , 82 , 83 , 84 ]. There is abundant evidence that root-associated microbes can help sustain plant growth under drought conditions [ 12 , 18 ]. However, no systematic study on the identity and PGP potential of upland rice root-associated microbes as well as their effects on drought tolerance exists.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scientists have isolated rhizospheric and endophytic bacteria and fungi from arid regions or from xerophytes, and these microbes have been shown to improve the growth of rice, sorghum, corn, cabbage, millet, and wheat under drought-stress conditions [ 14 , 80 , 81 , 82 , 83 , 84 ]. There is abundant evidence that root-associated microbes can help sustain plant growth under drought conditions [ 12 , 18 ]. However, no systematic study on the identity and PGP potential of upland rice root-associated microbes as well as their effects on drought tolerance exists.…”
Section: Discussionmentioning
confidence: 99%
“…A great variety of microbes are found to inhabit plant surfaces and different plant tissues and organs, including roots, rhizosphere, phyllosphere, stems, leaves, flowers, and seeds [ 7 , 8 , 9 ]. Root-associated microbes can improve host plant growth (such as N fixation [ 10 ], phosphate solubilization [ 11 ] and iron chelation), suppress pathogens, and mobilize some micronutrients, and they offer the potential to increase crop plant resilience to future drought [ 12 ]. Microbial-based plant biotechnology has been proven to be more effective than plant breeding and genetic improvement methods [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Increasingly the use of plant-associated microorganisms, especially rhizosphere-colonizing and endophytic bacteria and fungi, is being studied as a rapid and cost-effective strategy to augment the development of stress tolerant crop varieties ( Nadeem et al, 2014 ; Shrivastava and Kumar, 2015 ; Numan et al, 2018 ). It is well established that phytobiome members, especially rhizosphere and root dwellers, can play important roles in mediating abiotic stresses tolerance via promotion of plant growth, enhancement of nutrient availability, disease control, and modulation of plant abiotic stress signaling and response pathways ( Yang et al, 2009 ; Hardoim et al, 2015 ; Reinhold-Hurek et al, 2015 ; de Vries et al, 2020 ). With regard to salinity, previous studies focused on plant growth-promoting rhizobacteria (PGPR) showed that they may alleviate salinity induced osmotic stress, nutrient deficiency, oxidative stress, and ion toxicity via the production of bioactive compounds and modifications to the rhizosphere environment.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of drought stress on plants are mainly reflected in the effects on cell activity and organ and tissue function [ 1 , 2 ]. A decrease in the water content will result in the inhibition of photosynthesis, the slow growth of plants, and influence of the biomass or yield [ 3 ]. After drought stress, the metabolic process of cells is blocked, which leads to the accumulation of H 2 O 2 , 1 O 2 , and O 2 • − in cells [ 4 ].…”
Section: Introductionmentioning
confidence: 99%